Environmental factors affecting reproducibility of bioremediation field assays in Antarctica - Martinez Alvarez, Lucas Manuel; Ruberto, Lucas Adolfo Mauro; Gurevich Messina, Juan Manuel; Mac Cormack, Walter Patricio (Cold Regions Science and Technology)
Soil hydrocarbon-contamination represents an environmental threat even at remote locations such as Antarctica. In order to restore these soils, bioremediation, and biostimulation in particular, have proven to be an effective approach. However, large scale bioremediation schemes under the extreme environmental conditions of this continent provide a big uncertainty upon the robustness and reproducibility of these treatments. In this work, we compared the efficiency of two consecutive year field assays using 0.5 ton biopiles at Carlini Station, in order to identify those factors that affect the reproducibility of the pre-optimized biostimulation. First year field assay (biopiles I) reached >75% of hydrocarbon removal, while second year (biopiles II) only removed 55% of the total hydrocarbons. Several biological and physicochemical variables were statistically analyzed for both years' biopiles in order to identify the source of these differences. Total sunlight hours resulted to be the key factor driving removal efficiency in these treatments by increasing soil temperature inside the biopiles, and therefore, total biological activity and degrading bacterial counts in soil. This work represents the first study on the reproducibility of field assays in extreme environments such as Antarctica, and it provides a novel input to the scarce knowledge on field hydrocarbon bioremediation practices in cold regions. Fil: Martinez Alvarez, Lucas Manuel. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina. Universidad de Buenos Aires. Facultad de Farmacia y Bioquímica; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Houssay. Instituto de Nanobiotecnología. Universidad de Buenos Aires. Facultad de Farmacia y Bioquímica. Instituto de Nanobiotecnología; Argentina Fil: Ruberto, Lucas Adolfo Mauro. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional ...